AGE-DEPENDENT DYNAMICS OF COGNITIVE FUNCTIONS IN PRIMARY SCHOOLCHILDREN WITH DEFICIT OF AROUSAL REGULATION - T. V. Akhutina (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the analysis of age peculiarities of cognitive test performance in children with deficit function of arousal regulation. 173 primary school children participated in this study. We used the neuropsychological assessment and computer-based tests to show relation between different types of the deficit of arousal regulation (slowness or hyperactivity) and deterioration of indices of cognitive functions.